Yoga Exercise Fulfillment of the Sleep Needs in Elderly - Tintin Sukartini; Retno Indarwati; Anggraheni Anggraheni (Universitas Airlangga, 2008)
Introduction: Sleep disorder is one among problems faced by elderly. Yoga is one of methods which can be chose to fulfill the need of sleep. The objective of this study was to analyze the effect of yoga exercise on the fulfillment of the sleep needs in elderly. Method: The design used in this study was pre experimental. The population was elderly with sleep disorder in Panti Werdha Mojopahit Mojokerto. The sample was recruited using purposive sampling,15 respondents, taken according to the inclusion criteria. The independent variable of this study was yoga exercise and the dependent variable was the fulfillment of sleep in elderly. Data were collected by using structured questionnaire and the measurement of respondent vital sign, and were then analyzed using Wilcoxon Signed Rank Test and Paired t-Test with level of significance α≤0.05. Result: Result showed that yoga exercise increases the fulfillment the need of sleep beside it could reduce heart rate (p=0.001), and respiratory rate (p=0.001). Discussion: However, yoga exercise did not reduce of systolic (p=0.433) and diastolic blood pressure (p=0.055).